2017
DOI: 10.1177/1464420716689588
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir welding of aluminium alloys: An overview of experimental findings – Process, variables, development and applications

Abstract: The never ending appetite of the mankind to produce more and more competitive products results in continuous development of newer and newer manufacturing processes. One of such a kind, a solid state welding process highly appreciated for joining of a variety of aluminium and copper alloys, is friction stir welding. The process is also an accomplished method for joining dissimilar materials efficiently. The process finds its major application for joining hard-to-weld metals, especially the precipitation hardena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 201 publications
(311 reference statements)
0
33
0
2
Order By: Relevance
“…There are review papers available on FSW of same Al alloy joints, which discuss various aspects of the process such as tool design, process parameters, heat generation, microstructure and mechanical properties [4][5][6][7][8][9][10][11]. The number of research papers on FSW of dissimilar Al alloy joints published to date is shown in Figure 2 (search on December 15, 2017 found 68 papers from Web of Science).…”
Section: General Progress In Fsw Of Dissimilar Al-al Combinationsmentioning
confidence: 99%
“…There are review papers available on FSW of same Al alloy joints, which discuss various aspects of the process such as tool design, process parameters, heat generation, microstructure and mechanical properties [4][5][6][7][8][9][10][11]. The number of research papers on FSW of dissimilar Al alloy joints published to date is shown in Figure 2 (search on December 15, 2017 found 68 papers from Web of Science).…”
Section: General Progress In Fsw Of Dissimilar Al-al Combinationsmentioning
confidence: 99%
“…Moreover, some researchers [45][46][47] were focused on the thermography method which has been defined as a modern method for investigating the thermal field through online monitoring of the process, inspection and research. It should be mentioned that, this method is mainly used to determine the thermal field variations, when the measurements are difficult or impossible to record (i.e., inside the weld).…”
Section: Thermal Analysis Of Fsw (Friction Stir Welding)mentioning
confidence: 99%
“…When this tool rotates on a workpiece, friction occurred which generates the heat needed to plasticized the material at the joint interface, permitting the stirring of the material by the rotating tool pin. The pressure from the tool shoulder and the mixing of materials by the tool bonded the workpiece interface together [1][2][3][4][5][6][7][8]. The heat generated during FSW alters the mechanical properties of the weld through microstructural modifications.…”
Section: Introductionmentioning
confidence: 99%